2016
DOI: 10.1186/s12864-016-2731-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide alteration of 5-hydroxymenthylcytosine in a mouse model of Alzheimer’s disease

Abstract: BackgroundAlzheimer’s disease (AD) is the most common form of neurodegenerative disorder that leads to a decline in cognitive function. In AD, aggregates of amyloid β peptide precede the accumulation of neurofibrillary tangles, both of which are hallmarks of the disease. The great majority (>90 %) of the AD cases are not originated from genetic defects, therefore supporting the central roles of epigenetic modifications that are acquired progressively during the life span. Strong evidences have indicated the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 50 publications
5
28
0
1
Order By: Relevance
“…5hmC, the sixth base of genome, was revealed that it not only served as an intermediate embodied in DNA methylation pathway, but can also perform as a stable epigenetic marker to indicate the disease development . In this study, significant increase of 5hmC in 3 month‐age of AD mouse was found when compared with age‐matched WT control, demonstrating elevated 5hmC accumulation was positively correlated with the occurrence of AD and steadily presented in various stages of this disorder.…”
Section: Discussionsupporting
confidence: 92%
“…5hmC, the sixth base of genome, was revealed that it not only served as an intermediate embodied in DNA methylation pathway, but can also perform as a stable epigenetic marker to indicate the disease development . In this study, significant increase of 5hmC in 3 month‐age of AD mouse was found when compared with age‐matched WT control, demonstrating elevated 5hmC accumulation was positively correlated with the occurrence of AD and steadily presented in various stages of this disorder.…”
Section: Discussionsupporting
confidence: 92%
“…Different authors have described a decrease of 5mC or 5hmC levels in brains and blood samples in different animal models and human samples of these disorders [28][29][30][31][32][33][34][35]. Indeed, Aβ1-42 peptide reduces 5hmC levels in vitro [36]. Different brain regions have different 5hmC levels, with reduced 5hmC levels in the hippocampus but not in the cortex or cerebellum [36].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Aβ1-42 peptide reduces 5hmC levels in vitro [36]. Different brain regions have different 5hmC levels, with reduced 5hmC levels in the hippocampus but not in the cortex or cerebellum [36]. High hydroxymethylation regions are enriched in introns, exons and intergenic regions, and genes associated with these hydroxymethylated regions are implicated in neuronal development/differentiation and neuronal function/survival pathways [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…In conjunction with DNA methylation, hydroxyl-methylation regulates tissue-specific gene expression patterns [ 71 ]. Altered hydroxymethylation levels have been reported to occur in autism [ 72 ], Alzheimer's disease [ 72 ], intracerebral hemorrhage [ 73 ], and other conditions. Hydroxymethylation levels were affected by proton exposure [ 68 ] and chemotherapy [ 21 ].…”
Section: Discussionmentioning
confidence: 99%